Pengaruh Perceived Social Support terhadap Academic Help-Seeking pada Mahasiswa - Zahwa Zalfa Naira; Tati Tati; Muhammad Irsyad Naufal; Lucky Purwantini (Lembaga Pengembangan Kinerja Dosen, 2026)
University students frequently encounter academic challenges, including understanding course materials, completing assignments, and meeting academic deadlines, which may increase stress and reduce concentration, thereby affecting their willingness to seek academic assistance. Perceived social support has been considered a potential factor that encourages academic help-seeking behavior. This study aimed to examine the effect of perceived social support on academic help-seeking among university students. A quantitative correlational design was employed involving 1,062 active university students from 73 cities across 23 provinces in Indonesia, selected using convenience sampling. Data were collected using the Multidimensional Scale of Perceived Social Support and the Academic Help-Seeking Scale. Simple regression analysis was performed to examine the relationship between the variables. The results revealed that perceived social support did not have a significant effect on academic help-seeking behavior among university students (β = 0.021, p = 0.524, R² = 0.000). These findings indicate that perceived social support cannot be considered a predictor of students' tendency to seek academic assistance when experiencing learning difficulties. The study suggests that other psychological, personal, or contextual factors may play a more substantial role in influencing academic help-seeking behavior. Further studies are recommended to investigate additional variables that may better explain students' decisions to seek academic support.